Marital Status Of The Infertile Spouse In A Polygamous Marriage In Malaysia (Analysis Based On The Islamic Family Law Negeri Selangor In 2003 Section 23) - Nurul Husna Binti Malik Nasar; Amal Hayati (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The local community's rationale is somewhat troubled by the polygamy of an infertile spouse. This demonstrates the husband's egotism because it is the husband who is to blame, not the wife, for the absence of it. However, the fact is that many polygamous activities are still practiced by regular spouses in defiance of Islamic law, and as a result, many women continue to suffer due to their husbands' egocentric behavior. This type of polygamy also begs the logical concerns of why infertile husbands opt to practice it and what factors the Selangor Sharia Court Judge takes into account when rendering decisions in polygamy cases involving infertile husbands. However, there are extremely few of these marriages. The judge's decisions that are directly related to the Selangor State Court and also related to the primary studies are standard books, books of propositions and hadiths, the al-Qur'an, and Enactments of the Islamic Family Law in Malaysia are used in this writing study as secondary sources, providing additional information to support this discussion.